Household, maternal, and child related determinants of hemoglobin levels of Ethiopian children: hierarchical regression analysis - Shimels Hussien Mohammed; Tesfa Dejenie Habtewold; Ahmad Esmaillzadeh (BMC, 2019)
Abstract Background Anemia remains a major public health problem among children under five years old in Ethiopia, rising unexpectedly from 44% national prevalence in 2011 to 57% in 2016. In this study, we investigated the household, maternal and child-related dietary and non-dietary factors associated with hemoglobin (Hb) level of infants and young children. Method We analyzed data from a nationally representative sample of 2902 children aged 6-23 months, included in the 2016 Ethiopian demographic and health survey (EDHS). Hierarchical linear regression analysis was done to identify the factors associated with Hb level. We reported adjusted β (aβ) with 95% confidence interval (CI). Result Overall, 72% of children under 2 years of age were anemic in Ethiopia in 2016. Household factors: rich household wealth category (aβ = 0.48, 95%CI = 0.33-0.63, P < 0.001), and agrarian regions (aβ = 0.64, 95%CI = 0.40-0.88, P < 0.001) were significantly associated with a higher mean Hb level. Maternal factors: secondary and above education level (aβ = 0.69, 95%CI = 0.23-1.16, P = 0.004), and being not anemic (aβ = 0.40, 95%CI = 0.26-0.53, P < 0.001) were significantly associated with a higher mean Hb level. Child factors: age below 12 months (aβ = 0.72, 95%CI = 0.57-0.88, P < 0.001), female sex (aβ = 0.16, 95%CI = 0.03-0.30, P = 0.019), being not underweight (aβ = 0.22, 95%CI = 0.02-0.42, P = 0.031), average birth size (aβ = 0.25, 95%CI = 0.08-0.42, P = 0.003), no history of recent infection (aβ = 0.18, 95%CI = 0.02-0.33, P = 0.025), currently breastfeeding (aβ = 0.28, 95%CI = 0.12-0.44, P = 0.002), vitamin A supplementation (aβ = 0.17, 95%CI = 0.06-0.28, P = 0.021), and frequent meal feeding (aβ = 0.11, 95%CI = 0.05-0.16, P = 0.034) were significantly associated with a higher mean Hb level. Conclusion Hb level was associated with various dietary and non-dietary influences originating from household, maternal, and child levels. A comprehensive approach, addressing the multi-factorial nature of Hb status, might stand an important consideration to reverse the recent rise in anemia prevalence in Ethiopia.